Funcionalidad familiar y autoestima en estudiantes de secundaria de la Institución Educativa Teniente Manuel Clavero Muga, Punchana 2023 - Jesus Ruiz, Roxi Eperanza (2024)
The purpose of this study was to determine the relationship between family functionality and self-esteem of secondary school students of the I.E. Manuel Clavero Muga Punchana 2023. The type of research was basic with a quantitative approach of correlational scope and non-experimental cross-sectional design. Two instruments were used, the family functionality and self-esteem scale, with a stratified sample of 200 high school students. The results identified that family functionality is moderately, directly and positively related to self-esteem (rxy=0.571). Concluding, there is a significant relationship between family functionality and self-esteem of high school students of the I.E. Lieutenant Manuel Clavero Muga (p-value= 0.000<0.05).